Strategi Guru PAI dalam Mencegah Tindakan Perundungan di SMAN 1 Karangrejo Tulungagung - Nurul Karisma, Dewi; Khoulita, Ikfi (ILJ: Islamic Learning Journal, 2025)
The objectives of this study are: (1) To describe the strategies of Islamic Religious Education teachers in preventing acts of bullying through daily habits at SMAN 1 Karangrejo Tulungagung (2) To describe the strategies of Islamic Religious Education teachers in preventing acts of bullying through classroom learning at SMAN 1 Karangrejo Tulungagung (3) To describe the strategies of Islamic Religious Education teachers in preventing acts of bullying through learning outside the classroom at SMAN 1 Karangrejo Tulungagung. The design of this study uses a qualitative approach study research. The location studied was SMAN 1 Karangrejo Tulungagung. Data were collected through observation, in-depth interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawn. The results of this study show that: (1) Teacher strategy Islamic Religious Education in preventing acts of bullying through daily habits at SMAN 1 Karangrejo Tulungagung, by creating religious programs and setting an example for students, (2) Teacher strategies Islamic Religious Education in preventing acts of bullying through learning in the classroom at SMAN 1 Karangrejo Tulungagung, by conducting moral education and embedding the story of the Prophet in learning activities, and (3) Teacher strategies Islamic Religious Education in preventing acts of bullying through learning outside the classroom at SMAN 1 Karangrejo Tulungagung by creating a positive school climate, providing anti-bullying insights, giving reprimands and sanctions to children who commit acts of bullying, advising children with an emotional approach and notifying the families involved.